Efeito modulador da ouabaína no sistema imunológico - Carneiro, Luciana Teles (2011)
Initially known as a cardiotonic steroid capable to inhibit the Na+/K+ATPase, ouabain was identified as an endogenous substance present in human plasma, produced by the adrenal, pituitary and hypothalamus and can interfere with various aspects of immune response. In this study, which aimed to study the modulating effect of ouabain on the immune system in vivo and in vitro using mouse models, we demonstrated that treatment for three consecutive days using 0,56 mg/kg ouabain was able to reduce cell migration induced by mitogen Concanavalian A (Con A) to the peritoneum, and this fact reflects a decrease in the number of polymorphonuclear leukocytes, mainly neutrophils. In this same model, ouabain was also able to increase the number of mononuclear leukocytes in the peritoneal cavity. Evaluating the effect of treatment on lymphocytes in peripheral organs, we found that, in lymphocytes from mesenteric lymph nodes, this substance induces a decrease of 20% of T CD3+ lymphocytes, concomitant with an increase in same percentage of B lymphocytes, without, however, modulating the proportion of CD4+ and CD8+ among themselves, as well as the number of regulatory T cells (CD4+/CD25+). In the thymus, the same treatment, does not affect the proportion of lymphocyte subpopulations studied. The analysis qualitative and quantitatively of peripheral blood leukocytes, biometrics and cellularity of spleen, thymus and lymph nodes showed no change in response to ouabain treatment. Comparative studies using treatment for one or two days, with the same dose of 0,56 mg/kg did not trigger modulation, in vivo, in populations of T lymphocytes, B lymphocytes and subpopulations of CD4+ and CD8+ cells in mesenteric lymph nodes. In addition, ouabain was able to inhibit mitochondrial activity of lymphocytes stimulated with Con A, using MTT assay.These findings indicate an immunomodulatory role of ouabain.